Techno-economical evaluation of a hydrogen refuelling station powered by Wind-PV hybrid power system: A case study for Izmir-Cesme - Gokcek, Murat; Kale, Cihangir (Pergamon-Elsevier Science Ltd, 2018)
Hydrogen fuelling station is an infrastructure for the commercialisation of hydrogen energy utilising fuel cells, particularly, in the automotive sector. Hydrogen fuel produced by renewable sources such as the solar and wind energy can be an alternative fuel to depress the use of fuels based on fossil sources in the transport sector for sustainable clean energy strategy in future. By replacing the primary fuel with hydrogen fuel produced using renewable sources in road transport sector, environmental benefits can be achieved. In the present study, techno-economic analysis of hydrogen refuelling station powered by wind-photovoltaics (PV) hybrid power system to be installed in Izmir-Cesme, Turkey is performed. This analysis is carried out to a design of hydrogen refuelling station which is refuelling 25 fuel cell electric vehicles on a daily basis using hybrid optimisation model for electric renewable (HOMER) software. In this study, National Aeronautics and Space Administration (NASA) surface meteorology and solar energy database were used. Therefore, the average wind speed during the year was assessed to be 5.72 m/s and the annual average solar irradiation was used to be 5.08 kW h/m(2)/day for the considered site. According to optimisation results obtained for the proposed configuration, the levelised cost of hydrogen production was found to be US $7.526-7.866/kg in different system configurations. These results show that hydrogen refuelling station powered by renewable energy is economically appropriate for the considered site. It is expected that this study is the pre-feasibility study and obtained results encougare the hydrogen refuelling station to be established in Turkey by inventors or public institutions. (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen refuelling station; Renewable energy sources; Levelised cost of hydrogen; HOMER